THE EFFECT OF PICTURE SERIES MEDIA ON STUDENTS’ VOCABULARY MASTERY : - Rafli; Syatriana, Eny; Ardiana (English Language Teaching Methodology, 2024)
This research aimed to find out whether the use of picture series media effective in increasing students’ vocabulary mastery. The research applied a pre-experimental method with one group pretest posttest design and the data were collected by giving pre-test, treatment and post-test. The sample of the research was VIII 8 at MTs Ma’arif Puro’ro which consisted of 15 students in the academic year 2021/2022, the population of this study was 30 students consist of two classes in the first grade at MTs Ma’arif Puro’ro. The research sample was chosen using a purposive sampling technique. The vocabulary test words were employed to gather information.The researcher findings show that the mean score of the students’ in vocabulary is proved by post-test was 70.66% is higher than the mean score of the students’ in pre-test 40.00% and the value of the t-test is greater that t-table (t-test>t-table). Vocabulary was greater than t-table (13.440>1.753), It means that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. In other words, using picture series was effective in improving students’ vocabulary mastery in terms of verb and noun.